Pembentukan Karakter Religius Melalui Pembelajaran Berpusat pada Siswa Madrasah Aliyah Negeri - Sandria, Anis; Asy'ari, Hasyim; Siti Fatimah, Fahmi; Hasanah, Mizanul (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2022)
This article aims to describe how Islamic character building through student-centered learning and the role of stakeholders in through student-centered learning at MAN 1 Mojokerto. The type of this research is qualitative research that used a case study approach. Data were collected through observation, interviews, and documentation. The result of this research was: (1) Islamic character building through student-centered learning at MAN 1 Mojokerto, namely; (a) moral knowledge which was implemented through learning activities, (b) moral feeling through habituation, for example, discipline development and rewards or giving gifts and punishments, (3) moral action, which was formed through student-centered learning at MAN 1 Mojokerto, namely smiling, greeting, being polite and courteous, reading the Qur'an, praying before and after studying, enthusiastic and active in learning and maintaining tidiness and cleanliness. (2) The role of stakeholders in Islamic character building through student-centered learning at MAN 1 Mojokerto were: (a) Islamic teachers as educators, facilitators, motivators, administrators, and evaluators, (b) While parents as educators and mentors.